2014
DOI: 10.1155/2014/586159
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Diabetes, Body Mass Index, Hepatic Steatosis, and Risk of Liver Resection: Insulin Dependent Diabetes Is the Greatest Risk for Major Complications

Abstract: Background. This study aimed to assess the relationship between diabetes, obesity, and hepatic steatosis in patients undergoing liver resection and to determine if these factors are independent predictors of major complications. Materials and Methods. Analysis of a prospectively maintained database of patients undergoing liver resection between 2005 and 2012 was undertaken. Background liver was assessed for steatosis and classified as <33% and ≥33%. Major complications were defined as Grade III–V complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Severe steatosis did not significantly influence short‐term overall morbidity, major morbidity or mortality after partial hepatectomy in this study, which is in line with previous reports, but in contrast to findings in other studies. Patients with severe steatosis even showed a decreased occurrence of liver surgery‐specific complications.…”
Section: Discussionsupporting
confidence: 89%
“…Severe steatosis did not significantly influence short‐term overall morbidity, major morbidity or mortality after partial hepatectomy in this study, which is in line with previous reports, but in contrast to findings in other studies. Patients with severe steatosis even showed a decreased occurrence of liver surgery‐specific complications.…”
Section: Discussionsupporting
confidence: 89%
“…Despite some inconsistency in the literature [4,9,10], several articles have shown an increased risk for perioperative complications in obese patients undergoing hepatectomy [2,5e7]. In our cohort, neither obesity nor diabetes was identified as a major predictor of perioperative morbidity or mortality.…”
Section: Discussionmentioning
confidence: 71%
“…A total of six studies [2,[17][18][19][20][21] were identified in the systematic review that presented primary data comparing major postoperative complications between healthy weight vs overweight and obese patients following gastrointestinal surgery (Fig. 2).…”
Section: Systematic Reviewmentioning
confidence: 99%